Beyond the playlist: Looking at user‐generated collocation of cultural products through social tagging. Issue 1 (2013) - Desrochers, Nadine; Quan‐Haase, Anabel; Pennington, Diane Rasmussen; Laplante, Audrey; Martin, Kim; Spiteri, Louise
Abstract: Social tagging has become a common practice across a variety of platforms on the Web. In this panel, we propose to start with one title, Casino Royale, a James Bond novel by Ian Fleming, and the other cultural products that emanated from it (e.g., two movies, one song, visuals and images, articles and blog posts) to explore social tagging practices and other user‐generated content in a variety of different platforms. Goodreads, Last.fm, WordPress, Flickr and various library discovery systems will be used to expose the connections users establish between and among cultural products as well as to compare what tagging yields in different platforms. The results will be situated within the context of broader studies being performed by the panelists and audience members will be asked to contribute material for real‐time searches.